BALANCING DIGITAL HABITS: INVESTIGATING THE IMPACT OF SOCIAL MEDIA FREQUENCY ON COLLEGE STUDENTS’ READING COMPREHENSION IN INDONESIA - M. Bahly Basri; Muhammad Rapi; Sultan; Usman; Iin Nur Yasinta (LLDIKTI Wilayah X, 2024)
The percentage of social media users has an increasing trend and is problematic from a positive-negative impact perspective. The study aims to reveal the influence of social media frequency and the purpose of accessing social media on the reading comprehension skills of university students. Explanatory quantitative research was applied to 293 samples. The data were collected using questionnaires and objective tests. The results showed that students with moderate social media frequency (> 3 < 5 hours) had the best reading comprehension (mean rank: 161.68), while students with low social media frequency (< 3 hours) had the worst reading comprehension (mean rank: 134.55). The purpose of using social media to obtain information was the highest in the low frequency (n=109) and medium frequency (n=77) groups, while the purpose of obtaining entertainment was the highest in the high frequency group and the purpose of obtaining information took second place. The purpose of accessing information plays a role in the increase of insight that is a supporting factor for the performance of reading comprehension skills. The findings of this study recommend the implementation of digital literacy programs in education with the design of (a) integration in the curriculum, (b) moderate use of social media as a learning strategy, (c) development of usage guidelines, and (d) evaluation and monitoring of social media usage.